2016
DOI: 10.5335/rbceh.v13i1.5424
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de anemia em idosos internados em enfermarias gerais de um hospital universitário

Abstract: A anemia representa um problema de saúde pública para a população idosa, pois atua negativamente, sobretudo no contexto de hospitalização. Sua prevalência não está clara na literatura em virtude de resultados discrepantes. Os objetivos deste estudo foram avaliar a prevalência de anemia em idosos internados em enfermarias de clínica médica de um hospital universitário brasileiro, assim como determinar a classificação morfológica da anemia e sua distribuição de acordo com a faixa de idade e o sexo. Realizou-se u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
1
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
1
1
0
2
Order By: Relevance
“…These data, much higher than the findings in the non-institutionalized senile population, express the commitment of this vitality when not inserted in its social and family context From this perspective, in order to analyze the conditioning factors of the life and health situation, REDE (2008) affirms that the level of schooling can be used as an indicator of the socioeconomic status of the population. Several studies correlate a lower level of schooling with a higher prevalence of anaemia in the elderly, among which are Buffon et al (2015), Muñoz et al (2016), Costa et al (2016), Corona et al (2014), Milagres et al (2015) and Santos et al (2012). This fact is observed in the quantitative analysis of the schooling of the sample of the present study, which revealed a higher relative frequency of the elderly with the incomplete 1st grade, which was 55%.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…These data, much higher than the findings in the non-institutionalized senile population, express the commitment of this vitality when not inserted in its social and family context From this perspective, in order to analyze the conditioning factors of the life and health situation, REDE (2008) affirms that the level of schooling can be used as an indicator of the socioeconomic status of the population. Several studies correlate a lower level of schooling with a higher prevalence of anaemia in the elderly, among which are Buffon et al (2015), Muñoz et al (2016), Costa et al (2016), Corona et al (2014), Milagres et al (2015) and Santos et al (2012). This fact is observed in the quantitative analysis of the schooling of the sample of the present study, which revealed a higher relative frequency of the elderly with the incomplete 1st grade, which was 55%.…”
Section: Discussionsupporting
confidence: 73%
“…In this context, in a systematic review published by Gaskell et al (2008) that considered only those with 65 years or more, there was an average prevalence of anaemia of 47% in institutionalized elderly and 40% in those admitted to hospitals. Also, when analyzing elderly hospitalized in wards, the predominance of those with anaemia reaches 84%, according to Muñoz et al (2016). These data, much higher than the findings in the non-institutionalized senile population, express the commitment of this vitality when not inserted in its social and family context From this perspective, in order to analyze the conditioning factors of the life and health situation, REDE (2008) affirms that the level of schooling can be used as an indicator of the socioeconomic status of the population.…”
Section: Discussionmentioning
confidence: 99%
“…Em relação ao grau de gravidade da anemia, um estudo realizado com 193 pacientes idosos internados em enfermarias de clínica médica de um hospital italiano verificou que 48% dos pacientes apresentaram anemia leve a moderada e 4,1% anemia grave 16,17 . Em concordância, nosso estudo revelou uma maior prevalência de anemia moderada e leve entre os idosos, em contraste com anemia grave.…”
Section: Discussionunclassified
“…Pelo fato da anemia ser um sinal e não um diagnóstico etiológico, estabelecer sua causa é absolutamente necessário, a fim de implementação de terapia eficaz 16 . Poucos estudos têm investigado o perfil etiológico da anemia em pacientes hospitalizados 14 .…”
Section: Discussionunclassified